Islam in Malaysia: an entwined history - Aljunied, Syed Muhd Khairudin (Religion and global politics, 2019)
" This book surveys the growth and development of Islam in Malaysia from the eleventh to the twenty-first century, investigating how Islam has shaped the social lives, languages, cultures and politics of both Muslims and non-Muslims in one of the most populous Muslim regions in the world. Khairudin Aljunied shows how Muslims in Malaysia built upon the legacy of their pre-Islamic past while benefiting from Islamic ideas, values, and networks to found flourishing states and societies that have played an influential role in a globalizing world. He examines the movement of ideas, peoples, goods, technologies, arts, and cultures across into and out of Malaysia over the centuries. Interactions between Muslims and the local Malay population began as early as the eighth century, sustained by trade and the agency of Sufi as well as Arab, Indian, Persian, and Chinese scholars and missionaries. Aljunied looks at how Malay states and societies survived under colonial regimes that heightened racial and religious divisions, and how Muslims responded through violence as well as reformist movements. Although there have been tensions and skirmishes between Muslims and non-Muslims in Malaysia, they have learned in the main to co-exist harmoniously, creating a society comprising a variety of distinct populations. This is the first book to provide a seamless account of the millennium-old venture of Islam in Malaysia." --